Misconceptions Analysis on The Virus Chapter in Biology Textbooks for High School Students Grade X - Saputri, Dyah Ayu Febrianna; Widyaningrum, Trianik (International Journal of Active Learning, 2016)
Source of learning is something that can not be separated from the learning activities. One source of learning is learning materials. The book is one example of teaching materials from learning resources. The book is one source of information for learning. Problems often occur in the textbook is a misconceptions. This study aimed to analyze misconceptions on the virus chapter in biology textbook grade X. This research is a qualitative descriptive study provides the interpretation of data obtained in a rational and objective. This research subject is the content of the biology textbook for high school students grade X. While the object under study is the truth of the concept virus chapter biology textbook for high school students grade X. The results showed that the textbooks studied Biology class X are misconceptions which are divided into five categories, namely Misidentifications, Overgeneralizations, Oversimplications, Obsolete Concept and Terms and Undergeneralizations. Percentage of misconceptions found in every of biology textbook students grade X on the virus chapter that is 11.10% on the textbook A; 21.05% on the textbook B; and 31.03% on the textbook C. Criteria misconceptions most commonly found on the virus chapter in biology textbook students grade X is Oversimplications as much as 36.73%.